Początki polskiego romantyzmu w niemieckojęzycznych opracowaniach historycznoliterackich ostatnich lat - Stanisz, Marek (Wydawnictwo Uniwersytetu Śląskiego, 2018)
The article aim is to present the way the beginning of Polish Romanticism (1818–1830, so-called ‘Romantic turn’) is presented by German critical publications appearing in recent years. The article author analyses the narration on Polish Romanticism within German conceptions of Polish literary development and European Romanticism evolution and examines the categories that determine such narrations. It leads to a conclusion that the beginnings of Polish Romanticism are presented in two different ways. German scholars focus either on the influence (cultural transfer) of German literature and aesthetic doctrine or on a more complex model explaining the functioning of early Romantic tendencies in Poland (which includes various foreign inspirations, the existence of Polish literary tradition and the interest in folk culture). However, many German syntheses of European Romanticism do not refer to Polish literature at all.

Przedmiotem artykułu jest odpowiedź na pytanie, w jaki sposób niemieckojęzyczne opracowania historycznoliterackie ostatnich lat ukazują początkową fazę kształtowania się romantyzmu w Polsce (1818-1830), czyli tzw. przełom romantyczny. Autor analizuje miejsce narracji o początkach polskiego romantyzmu w ramach niemieckojęzycznych koncepcji rozwoju literatury polskiej oraz ewolucji romantyzmu w Europie, a także bada kategorie historycznoliterackie, którym podporządkowane są te narracje. Przegląd ten skłania do wniosku, że początki romantyzmu w Polsce są przedstawiane na dwa sposoby. Niemieccy badacze skupiają się albo na wpływie (lub transferze kulturowym) niemieckiej literatury i myśli estetycznej na polskich twórców, albo na bardziej złożonym obrazie formowania się nowych tendencji literackich w Polsce (w którym ważną rolę odgrywają różnorodne inspiracje zagraniczne, a także ciśnienie polskiej tradycji literackiej oraz fascynacja kulturą ludową). W wielu niemieckojęzycznych syntezach romantyzmu europejskiego polska literatura jest jednak całkowicie pomijana.
The Beginnings of Polish Romanticism Presented in German Critical Studies in Recent Years
Keywords: Polish romanticism; reception of Polish literature; Romantic turn; polski romantyzm; recepcja literatury polskiej; przełom romantyczny